Isolation and characterization of an immunogenic fragment of heat shock protein 60 from Trichophyton mentagrophytes - Raska, M; Zemanova, E; Kafkova, L; Belakova, J; Vudattu, N K; Kopecek, P; Weigl, E (Mycoses, 2004)
Heat shock protein 60 (hsp60) were isolated from several fungal, protozoal and many bacterial pathogens and successfully used for protective vaccination in some infection models. This work focuses on the isolation of recombinant hsp60 from the dermatophyte, Trichophyton mentagrophytes as a potentially protective antigen in trichophytosis. With the help of a previously tested set of degenerated primers, it was used reverse transcriptase polymerase chain reaction (RT-PCR) for isolation of partial cDNA of the hsp60 T. mentagrophytes (labelled hsp60-TM814), which was cloned into cloning vector. The sequencing of hsp60-TM814 cDNA and global alignment confirmed homology of the hsp60-TM814 with other members of the hsp60 family. Hsp60-TM814 cDNA corresponds to the region encoding the immunoprotective fragment of the hsp60 from Histoplasma capsulatum, used successfully in mouse model of histoplasmosis. A recombinant fragment (r-hsp60-TM664), 220 amino acids in length, was prepared in a prokaryote expression system, and its identity confirmed by mass spectroscopy. High immunogenicity of r-hsp60-TM664 was proven after subcutaneous immunization of mice. Immunized mouse sera recognized r-hsp60-TM664 on Western blots as well as hsp60 from mouse liver lysate and lysate of Candida albicans.
Keywords: chaperon hsp60; Recombinant Proteins; sekvence nukleotidů; Histoplasma; DNA, Fungal; Chaperonin 60; Sequence Analysis, DNA; Candida albicans; komplementární DNA; sekvenční analýza DNA; Fungal Proteins; molekulární sekvence - údaje; Amino Acid Sequence; Sequence Homology, Amino Acid; sekvenční seřazení; sekvenční homologie aminokyselin; DNA fungální; rekombinantní proteiny; Trichophyton; sekvence aminokyselin; Molecular Sequence Data; Base Sequence; DNA, Complementary; fungální proteiny; Sequence Alignment